Rancang Bangun Sistem Informasi Akuntansi Pada Perusahaan Jasa Reparasi - Erawati, kadek nonik; Suryana, I Gede Putu Eka (INFOTEKS (Information Technology, Computer and Sciences), 2021)
An industry that is engaged in repair is an industry that is engaged in goods and special services, namely serving hardware, IT Consulting, network installation, and CCTV. The problem that occurs is accounting difficulties in managing transaction data because accounting is required to recap transaction information taken from different Microsoft Excel sheets or files. Not only that, but the manual process in making accounting reports also takes time so there can be delays in making accounting reports and errors when structuring accounting reports. Based on the above background, the formulation of the problem in the research is How to Design and Build an Accounting Data System in an Industry that is engaged in repairs, on the other hand, the research objective to be achieved in the reporting process is being able to design and build an industrial accounting information system. The result of this research is to create a system that can digest customer information, supplier information, account information, universal daily information, transaction information, user information, and accounting reports. This system is expected to help accountants in making accounting reports to identify the state of industry accounting